2016
DOI: 10.5513/jcea01/17.3.1773
|View full text |Cite
|
Sign up to set email alerts
|

Solid matrix priming with chitosan enhances seed germination and seedling invigoration in mung bean under salinity stress

Abstract: The objective of present study was to evaluate the response of the mung bean seeds of 'Sonali B1' variety primed with chitosan in four different concentrations (0, 0.1%, 0.2% and 0.5%) under salinity stress of five different concentrations (i.e., 0, 4, 6, 8 and 12 dS*mm-1) and halotolerance pattern by applying Celite as matrix at three different moisture levels (5%, 10% and 20%). Improved germination percentage, germination index, mean germination time, coefficient of velocity of germination along with root an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…Fig 3 a and b clearly indicate that elevated levels of moisture stress induced by PEG-6000 results to reduced TI % that directly affect the seedling vigour index and ultimately suppress the establishment of healthy seedling growth. The almost similar results were also reported by Sen and Mandal, (2016); Qaiser et al (2014). While priming treatment again trying to improves T. I.…”
Section: Length Of Shoot or Root In Which Treatment Appliedsupporting
confidence: 90%
See 1 more Smart Citation
“…Fig 3 a and b clearly indicate that elevated levels of moisture stress induced by PEG-6000 results to reduced TI % that directly affect the seedling vigour index and ultimately suppress the establishment of healthy seedling growth. The almost similar results were also reported by Sen and Mandal, (2016); Qaiser et al (2014). While priming treatment again trying to improves T. I.…”
Section: Length Of Shoot or Root In Which Treatment Appliedsupporting
confidence: 90%
“…Zhang et al (2015) pointed that influence of moisture stress induced by PEG-6000 may be recovered by seed priming treatment. The similar result was also reported by Pant and Bose, (2016); Sen and Mandal, (2016). W hile Jhanji and Dhingra (2018) reported that seed priming with thiourea not only improved seed germination, seedling vigour index but also improving tolerance index in both root and shoot Yadav et al (2011).…”
Section: Length Of Shoot or Root In Which Treatment Appliedsupporting
confidence: 83%
“…Chitosan (Cs) has a wide application scope in various biological fields including agriculture, thanks to its amine and -OH groups which make it with nucleophilic behavior and easily available for various chemical reaction (Rabêlo et al, 2019). The application of Cs in the right manner and concentration can effectively reduce the harmful effects of high salinity levels and increase plant growth and/or the yields (Safikhan et al, 2018), as it reported on maize (Turk, 2019), mung bean (Sen & Mandal, 2016), rice (Garude, Vemula, & SRM, 2019), safflower (Golkar, Taghizadeh, & Yousefian, 2019), stevia (Gerami et al, 2020), sunflower (Bakhoum, Sadak, & Badr, 2020), and tomato Ullah et al, 2020) plants. Those studies also showed that Cs under saline stress alleviated effect at gene expression level as well as in biochemical level.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is characterized by the increased production of reactive oxygen species which leads to unspecific oxidation of proteins and membrane lipids, causing DNA injuries (Schützendübel and Polle, 2002). Plant salt stress has been frequently studied, usually focusing on certain plant physiological aspects affected by the salinity; however, from the agronomical perspective, it is especially important to conduct research addressing the issue of salinity effect on crop productivity, i.e., growth, development and yield (Sen and Mandal, 2016).…”
Section: Introductionmentioning
confidence: 99%